2021
DOI: 10.4196/kjpp.2021.25.6.533
|View full text |Cite
|
Sign up to set email alerts
|

Triptolide improves myocardial fibrosis in rats through inhibition of nuclear factor kappa B and NLR family pyrin domain containing 3 inflammasome pathway

Abstract: Myocardial fibrosis (MF) is the result of persistent and repeated aggravation of myocardial ischemia and hypoxia, leading to the gradual development of heart failure of chronic ischemic heart disease. Triptolide (TPL) is identified to be involved in the treatment for MF. This study aims to explore the mechanism of TPL in the treatment of MF. The MF rat model was established, subcutaneously injected with isoproterenol and treated by subcutaneous injection of TPL. The cardiac function of each group was evaluated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 53 publications
0
9
0
1
Order By: Relevance
“…Acute inflammation plays a crucial role in diverse cardiac injuries, including the participation in the regulation of cardiac remodeling after myocardial infarction [ 6 - 8 ]. In the present study, we found that there is high IL-6 expression in cardiac fibroblasts triggered by myocardial infarction.…”
Section: Discussionmentioning
confidence: 99%
“…Acute inflammation plays a crucial role in diverse cardiac injuries, including the participation in the regulation of cardiac remodeling after myocardial infarction [ 6 - 8 ]. In the present study, we found that there is high IL-6 expression in cardiac fibroblasts triggered by myocardial infarction.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, TP induces GSDME-mediated pyroptosis of head and neck tumor cells by inhibiting mitochondrial hexokinase-ΙΙ [ 74 ]. Moreover, TP could prevent IgAN progression [ 75 ] and improve myocardial fibrosis by down-regulating NLRP3 inflammasomes [ 76 ]. Overall, this study strengthens the idea that TP may inhibit the inflammatory response and reduce the pyroptosis of renal podocytes in DN through the NLRP3 inflammasome pathway.…”
Section: Discussionmentioning
confidence: 99%
“…[ 11 ] have reported that not only does β-sitosterol reduce the level of inflammatory mediators in mice such as tumor necrosis factor (TNF-α), and interleukin 6 (IL-6), etc ., but it remarkably improved the antioxidative activities such as glutathione (GSH) and catalase (CAT), etc . Myocardial fibrosis rat models were treated with triptolide, NF-kB pathways were inhibited, and NLRP3 inflammasomes were activated to improve myocardial fibrosis in rats [ 12 ]. In vivo / vitro experiments in mice with myocardial infarction have indicated that Nobiletin reduced myocardial fibrosis and apoptosis by activating PPARγ and PGC1α [ 13 ].…”
Section: Discussionmentioning
confidence: 99%